A new species of Kana Distant representing the first record of Evacanthinae (Hemiptera: Cicadellidae) from Madagascar - Dietrich, Christopher H. (Zootaxa, 2023)
Kana ranomafanensis sp. n. is described and illustrated based on specimens from montane rainforests in eastern Madagascar. This is the first record of the diverse and widely distributed leafhopper subfamily Evacanthinae from Madagascar. A revised diagnosis of Kana Distant is provided and the new species is compared to species from the Indomalayan and Afrotropical regions. Evidence from previous molecular divergence time analyses suggests that ancestors of the new species arrived in Madagascar via transoceanic dispersal. The ovipositor of the genus and the male genitalia of Kana decora (Melichar), previously known only from the female holotype from Sri Lanka, are illustrated for the first time.